Unsymmetrical pyrazole-based new semiconductor oligomer: synthesis and optical properties - Çetin, A.; Gündüz, Bayram; Menges, N.; Bildirici I. (Springer Verlag, 2017)
Poly(p-phenylene-1-(2,5-dimethylphenyl)-5-phenyl-1H-pyrazole-3,4-dicarboxy amide) (poly(PDPPD)) was synthesized from reactions of p-phenylene-diamine and 1-(2,5-dimethylphenyl)-5-phenyl-1H-pyrazole-3,4-dicarbonyl dichloride (monomer) by heating under solvent. This newly synthesized poly(PDPPD) was characterized by 1H, 13C-NMR, FT-IR, gel permeation chromatography (GPC). In addition, we investigated optical properties of the poly(PDPPD) containing the substituted pyrazole ring at different molarities. The average transmittance (Tavg) values of the poly(PDPPD) in the visible (V) region were higher than the Tavg values in the near-ultraviolet (NU) region. The Tavg values of the poly(PDPPD) in the NU and visible (V) region decreased with increasing molarity. The absorption band edge (Absbe) value of the poly(PDPPD) decreased with increasing molarity. It was observed that the optical band gap (Eg) of the poly(PDPPD) value decreased more with increasing molarity. The refractive index of the poly(PDPPD) decreased with increasing wavelength and decreasing molarity. The structure of the poly(PDPPD) in the lowest energy was optimized by DFT calculation and its HOMO–LUMO orbitals were plotted. © 2016, Springer-Verlag Berlin Heidelberg.
Keywords: HOMO–LUMO; Oligomer; Optical band gap; Optical constant; Poly-pyrazole; Refractive index